2010
DOI: 10.3725/jjn.40.7
|View full text |Cite
|
Sign up to set email alerts
|

A simple method to collect phoretically active dauer larvae of Caenorhabditis japonica

Abstract: Caenorhabditis japonica is a bacterial-feeding nematode phoretically associated with the shield bug, Parastrachia japonensis. Caenorhabditis japonica dauer larvae (DLs) are mainly found on adult female bugs throughout the year, suggesting an intimate association between the nematode and the shield bug, but the mechanisms of the female bug-specific association, as well as the life history of C. japonica, are not well known. To understand the biology of C. japonica and the behavior of DLs, we developed a simple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…Dog food agar (DFA) medium (Hara et al, 1981) seeded with E. coli OP50 was used as a nutrient-rich medium to obtain a large number of DL. Nictating C. japonica DL were exclusively collected as described by Tanaka et al (Tanaka et al, 2010). Briefly, a sterile yellow 200μl pipet tip (Watson, Fukaekasei Co., Tokyo, Japan) was vertically placed, such that the tapered side was up, at the center of a 100ml culture bottle of DFA medium, and E. coli OP50 and the nematodes were cultured at 25°C.…”
Section: Materials and Methods Nematodesmentioning
confidence: 99%
See 1 more Smart Citation
“…Dog food agar (DFA) medium (Hara et al, 1981) seeded with E. coli OP50 was used as a nutrient-rich medium to obtain a large number of DL. Nictating C. japonica DL were exclusively collected as described by Tanaka et al (Tanaka et al, 2010). Briefly, a sterile yellow 200μl pipet tip (Watson, Fukaekasei Co., Tokyo, Japan) was vertically placed, such that the tapered side was up, at the center of a 100ml culture bottle of DFA medium, and E. coli OP50 and the nematodes were cultured at 25°C.…”
Section: Materials and Methods Nematodesmentioning
confidence: 99%
“…During in vitro culture of C. japonica on artificial medium, newly produced DL show active upward migration and nictation (Tanaka et al, 2010) (supplementary material Movies1, 2), and these behaviors seem to be useful for the nematodes to increase their opportunities of encountering and embarking onto host insects wandering on leaf litter. Because nictating DL migrate up, against the direction of gravity, onto their host insects and accumulate readily on pipette tips, we hypothesized that nictating DL could show negative gravitactic behavior.…”
Section: Introductionmentioning
confidence: 99%
“…We also compared the behavioral changes in C. japonica DL during their association with P. japonensis. Upward movement of C. japonica DL was observed during nematode culture (Tanaka et al, 2010a), which suggested negative gravitaxis in C. japonica, although DL on the carrier insect had to move downward from their carrier. We hypothesized that the gravitactic behavior of C. japonica changed during the association, and thus, we compared the gravitactic behavior of DL and its possible role in disembarkation.…”
Section: Introductionmentioning
confidence: 99%
“…C. japonica DL were maintained on dog food agar medium (Hara et al, 1981) seeded with Escherichia coli strain OP50 at 25 . Phoretically active DL were collected as described by Tanaka et al (2010a). In brief, to collect DL, a sterile yellow 200-µl pipette tip (Watson, Fukaekasei Co., Ltd., Kobe) was vertically placed in dog food agar in a 100-ml culture bottle.…”
Section: Nematodes and Insectsmentioning
confidence: 99%
“…Dog food agar medium (Hara et al, 1981) seeded with Escherichia coli (Migula) Castellani and Chalmers OP50 was used to obtain a large number of nematodes. Nictating C. japonica DL were collected as described previously (Tanaka et al, 2010). In brief, a sterile yellow 200 μl pipet tip (Watson, Fukaekasei Co., Ltd, Tokyo, Japan) was vertically placed such that the tapered side was up at the centre of a 100 ml culture bottle of dog food agar medium in which E. coli OP50 and the nematodes were inoculated.…”
Section: Nematodesmentioning
confidence: 99%